PENGARUH PREFERENSI KONSUMEN TERHADAP PEMBELIAN BUAH APEL IMPOR DI HYPERMART PALU GRAND MALL - Muh Fahruddin Nurdin; Hadayani Hadayani; Lien Damayanti (Universitas Tadulako, 2017)
The objectives of the research was to analyze the influence of price, taste, color, texture and size of imported apple fruit on consumers’ preferences and on the purchase of the fruit, and to analyze the influence of attributes to the purchase of the fruit in Hypermart Palu Grand Mall. The research location was purposively determined in Hypermart considering that itis the largest site where imported fruit are sold in Palu city. Samples of 50 people were selected using an Accidental Sampling method based on spontaneity factor. The results of analysis showed that the coefficient of attribute lines of price, taste, color, texture, and size statistically affected the volume of the imported apple sold in the Mall. The variables (Xi) of price, taste, color, texture and size simultaneously affected the purchase variable (Y) significantly at 87.7% or R2 = 0.877 whereas the effect of other factors not included in this research was 0.123 or 12.3%. The proportional effects on the fruit purchase for the taste variable was 0.799 or 79.9, the size was 0.023 or 2.3%, the color was 0.021 or 2.1%, the texture 0.016 or 1.6% and the price was 0.019 or 1.9%.Keywords : Consumer Preferences, and Imported Apple Fruits.